2015
DOI: 10.5152/tjar.2014.93824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Intravenous Magnesium Sulphate Treatment on the Spinal Anaesthesia Produced by Bupivacaine in Pre-eclamptic Patients

Abstract: Objective: In our study, the effect of intravenous magnesium sulphate in normal and pre-eclamptic patients on spinal anaesthesia produced by bupivacaine was investigated.Methods: Sixty-four pregnant (32 normal and 32 pre-eclamptic) were accepted in this study. Pregnants were divided into four groups as patients given intravenous magnesium sulphate and as control. Spinal anaesthesia was induced with 12.5 mg 0.5% hyperbaric bupivacaine. Intraoperative and postoperative haemodynamic variables, sensorial block per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Besides, block duration was shortened that led to increasing the need for initial analgesia. [7] In another study by Shah and Dhengle, results showed that sensory and motor block were, respectively, shorter about 34 min and 25 min in the control group. Postoperative requirement to analgesia in magnesium group was lower than control group (33% vs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, block duration was shortened that led to increasing the need for initial analgesia. [7] In another study by Shah and Dhengle, results showed that sensory and motor block were, respectively, shorter about 34 min and 25 min in the control group. Postoperative requirement to analgesia in magnesium group was lower than control group (33% vs.…”
Section: Discussionmentioning
confidence: 99%
“…about effect of continuous magnesium sulfate infusion on spinal block characteristic;[6] in a study by Mustafa et al . about the effect of intervenous magnesium sulfate treatment on the spinal anesthesia produced by bupivacaine preeclamptic patients;[7] and in a study by Shah and Dhengle about magnesium sulfate for postoperative analgesia after surgery under spinal anesthesia. [8]…”
Section: Introductionmentioning
confidence: 99%